Pelaksanaan Tugas Syahbandar di Kantor Kesyahbandaran dan Otoritas Kelas III Pelabuhan Sungai Duku Pekanbaru - Hendry Andry; Anggraini Dwi Milandry (Yayasan Literasi Sains Indonesia, 2023)
This research aims to find out about the implementation of the harbormaster's duties at the Class III Harbormaster and Authority Office of Sungai Duku Port, Pekanbaru. The research method used is descriptive qualitative, uses interviews, observations and is supplemented by literature study. In this research, the author uses four indicators to describe the success or failure of the harbor master in carrying out his duties, namely communication, resources, disposition and bureaucratic structure indicator's. The results of this research are that the implementation hasn't been carried out optimally. This is because the communication between Harbormaster's Office officers and passengers is limited to checking passenger tickets and providing ship departure schedules. Then, direct physical feasibility tests of ships cannot be carried out thoroughly, due to a lack of human resources. Furthermore, there is a lack of awareness among officers regarding the implementation of all their obligations. In terms of, the bureaucratic structure indicator's has been, actually formed as it should be, but in practice, even though the tasks have been carried out in accordance with the respective division of tasks, but in fact the implementation still not effective and efficient.